Analisis Spasial Kenaikan Tinggi Permukaan Air Batang Sumani Menggunakan Model Permukaan Digital - Alfansyuri, Era; Agus, Indra (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2023)
The occurrence of flooding in the Batang Sumani area of ​​Solok Regency is caused by several things, including the low slope of the river, the river cross-section which is not wide enough, the topography of the plains, heavy bends along the river and silting due to sedimentation and the vulnerability to flood hazards which is quite high in the watershed area. The influence of the topography of the plains causes inundation on land managed and used by the community. In accordance with technological developments in digital mapping of the earth's surface, the earth's surface can be presented in the form of a three-dimensional map called a Digital Elevation Model (DEM). This DEM is used as a model, analysis and representation of conditions related to the earth's surface. The use of DEM in the process of analyzing inundation caused by surface runoff will help in identifying the coverage of inundation areas and water catchment areas. By using the Simulate water level rise / flooding analysis from the Global Mapper application it is possible to simulate water level rise / flooding which makes it possible to simulate the coverage or spread of water/flooding by increasing the water level to a certain depth and spatial analysis using the Geographic Information System can see the influence of the inundation area on land use managed by the community around the inundation area. So that the location and coverage of the inundation on land use can be obtained. Most of the inundation areas are in garden areas at 37.56%, rice fields at 23.83%, fields at 24.03% and residential areas at 13.67%. There was a significant increase in the water level rise of 2 meters.